О задании ограничений в задаче оптимизации системы утилизации вторичного гидроэнергетического ресурса - Качан, Ю. Г.; Коваленко, В. Л. (НТУ "ХПИ", 2009)
To apply the method of «pattern» recognition for putting in limits (forbidden zones) on the places of elements’ location in a system of secondary hydroenergetic plants resource collection is proposed in this article. In math meaning the forbidden zones are proposed to make by forming a dividing function «pattern». Its simplest analytical description is a signature function in our case. In offered approach will help to solve and simplify the task of optimization the system of collection without solving hard topologies tasks.
Keywords: гидроэнергетика; вторичный ресурс; утилизация; сбор технической воды; гидроресурс